ADVANCED HIGH-FREQUENCY SIGNAL INJECTION TECHNIQUES FOR RELIABLE SENSORLESS OPERATION OF PMSM AT LOW SPEEDS - Tanaka, Haruto (Ayden International Journal of Basic and Applied Sciences, 2024)
Permanent Magnet Synchronous Motors (PMSM) are highly favored by major electric vehicle manufacturers due to their simple construction, compact size, lightweight, and superior efficiency. However, traditional sensorless control methods based on fundamental excitation mathematical models encounter limitations, especially at low motor speeds, where extracting reference signals becomes challenging. This obstacle can lead to difficulties in accurately determining the rotor position, resulting in detection failures. To overcome these issues, a sensorless control strategy based on high-frequency signal injection has emerged. This innovative approach relies less on mathematical parameters and motor models, offering enhanced robustness and stability. In particular, it effectively compensates for the shortcomings of fundamental excitation mathematical models when PMSMs operate at low speeds